Venture Capital and Strategic Investment for Developing Government Mission Capabilities - Webb, Tim (RAND Corporation, 2014)
To address urgent operational needs in a changing threat environment, this report examines one type of government acquisition method, called government strategic investment (GSI). Through a combination of case studies and economic modeling, this research will help government acquisition managers judge the suitability of strategic investment methods for motivating future government mission-oriented innovation by private firms.